What do children with Specific Language Impairment do with multiple forms of DO? - Rice, Mabel L. (2012)
PURPOSE: This study was designed to examine the early usage patterns of multiple grammatical functions of DO in children with and without SLI. Children’s use of this plurifunctional form is informative for evaluation of theoretical accounts of the deficit in SLI. METHODS: Spontaneous uses of multiple functions of DO were analyzed in language samples from 89 children, 37 children with SLI age 5;0–5;6, 37 age-equivalent children, and 15 language-equivalent children, age 2;8–4;10. Proportion correct as well as the types of errors produced were analyzed for each function of DO. RESULTS: Children with SLI had significantly lower levels of proportion correct Auxiliary DO use compared to both control groups, with omissions of the DO form as the primary error type. Children with SLI had near-ceiling performance on Lexical DO and Elliptical DO, similar to both control groups. CONCLUSIONS: Plurifunctionality is not problematic: children acquire each function of DO separately. Grammatical properties of the function, rather than surface properties of the form, dictate whether SLI children will have difficulty using the word. Overall, these results support the Extended Optional Infinitive account of SLI, and the use of difficulty with Auxiliary DO as part of a clinical marker for SLI.